2014
DOI: 10.3109/0886022x.2014.967645
|View full text |Cite
|
Sign up to set email alerts
|

The impact of alpha-lipoic acid on amikacin-induced nephrotoxicity

Abstract: Amikacin (AK) is an antibacterial drug, but it has remarkable nephrotoxic and ototoxic side effects due to increase in reactive oxygen radicals. This study was established to determine the possible protective effects of alpha-lipoic acid (ALA), a powerful antioxidant, on AK-induced nephrotoxicity. Three different groups of rats (n ¼ 6) were administered saline (control), AK (1.2 g/kg, intraperitoneally), ALA (100 mg/kg, p.o.) and AK combination (ALA one day before the AK for five days). Renal function, oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…12,13,26 DNA, in particular, is more susceptible to attack by reactive oxygen species than proteins and membrane lipids, which are protected by lowmolecular weight anti-oxidants and anti-oxidant enzymes. Among many types of oxidative DNA damage, 8-OHdG is one of the most abundant oxidative products of cellular DNA.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,26 DNA, in particular, is more susceptible to attack by reactive oxygen species than proteins and membrane lipids, which are protected by lowmolecular weight anti-oxidants and anti-oxidant enzymes. Among many types of oxidative DNA damage, 8-OHdG is one of the most abundant oxidative products of cellular DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies have shown that tubular necrosis is the main cause of nephrotoxicity (Asci et al 2015;Parlakpinar et al 2004). Glomerulus obstruction, proin ammatory cell migration, tubule dilatation, bleeding, and tubule degeneration were observed in the AK-induced nephrotoxicity group (Asci et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As an example of antioxidant drugs, alpha-lipoic acid neutralizes ROS and restores inactivated natural antioxidants, such as vitamin C, with promising results in animal studies [99,100]. Selenium supplementation is proposed to reduce cellular oxidative damage in animal models.…”
Section: Perspectives On Pharmacological Treatmentmentioning
confidence: 99%